088 GOSH teens career festival. (December 2018) - Parish, E; Hothi, D; Simpson, S
Abstract : Background: Adolescence is a time of great change and opportunity as young people develop their personal identity and cultivate future career ideas. Often the Young People we care for at GOSH miss some key educational opportunities while receiving treatment, including career planning and advice. We wanted to run a co-created programme, which met the needs of this group of Young People to help their transition. Project summary: (Work in progress) During June–July 2017, we ran a pilot scheme to deliver life skills experience days for Young People at GOSH. Feedback from these sessions was a request for more events, with varied professions and career opportunities to be represented. There was also a theme of specialist advice needed for those who have long-term health conditions, in particular how to address health needs in the workplace and at the interview. We formed a working group of GOSH staff, young people representatives, GOSH Charity and Education. We liaised with the transition working group team and developed a Careers Festival for current and past patients (https://www.gosh.org/gosh-careers-festival-0). The day event is open to 14–18 year-olds and consists of drop-in sessions with a range of external companies coming to support attendees in CV writing, interview practice and talks from former patients and employees about working with long-term conditions and disability in the workplace. Results: This is a work in progress with our main event being held on 3 August 2018. We expect to be able to report on the event outcome (attendees and results of feedback) ahead of the GOSH conference. We are utilising quality improvement methodology to assess the success of this project and if felt to be worthwhile to anticipate this to be an annual event. Acknowledgments: Special thanks to GOSH Charity and GOSH Working Group for GOSH Teens Career Festival: (Jacqui Segal, Oliver Field, Daljit Hothi, Amy Sutton, Emma Parish, Nigel Mills, Jayne Franklin, Prisha Bathia, Laura Walsh, Tanya Whitehead, Emma Ninnis, Kelechi Gideon).